Impacts of Cycled Dietary Protein Ratios on the Growth Performance and Somatic Indices of Meagre (Argyrosomus regius) - Derya Güroy; Onur Karadal (Aquatic Sciences and Engineering)
Protein is both an essential and a costly nutrient in aquafeeds. In this study, the effects of different cyclic protein ratios on growth performance, biological indices, and profitability of meagre (Argyrosomus regius) were investigated. Diets which included 48, 44, and 40% protein ratios were prepared, and the experimental groups were designed by cyclical periods of 48% for 12 weeks (P48, control), 40% for 6 weeks + 48% for 6 weeks (P40/48), and 44% for 6 weeks + 48% for 6 weeks (P44/48). The study was carried out with three replicates for 12 weeks in nine 450 L fiberglass tanks connected to a recirculating marine water system. Meagre with an average weight of 49.93±0.35 g were kept with 10 fish per tank. At the end of the study, the best weight gain was observed in the P48 group compared to the other treatments (P<0.05). However, no statistical differences were found between the specific growth rates and feed conversion ratios of the experimental groups (P>0.05). In addition, both condition factor and viscerosomatic index were higher in P44/48 and P40/48, respectively (P<0.05). In conclusion, aquafeeds with a protein content of 48% can be circulated for short periods as part of 40% protein diets.